EARLY DIAGNOSTIC DIFFERENTIATION IN NEONATAL CHOLESTASIS TO OPTIMIZE THERAPEUTIC OUTCOMES - Dr. Priyadarshini M R (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Neonatal cholestasis represents a category of diseases which frequently manifest with comparable clinical symptoms, and it is difficult to provide their precise diagnosis, yet it is crucial to do so to ensure adequate management. It is important to distinguish these conditions by the study of liver biopsy samples to influence adequate treatment approaches. We assessed the clinical features, laboratory results, and histopathological features of pretreatment liver biopsy specimens of infants with biliary atresia (n=66), intrahepatic bile duct paucity (n=15) and neonatal hepatitis (n=21) in the current study. Gender distribution was almost even in patients with biliary atresia and intrahepatic bile duct paucity but the neonatal hepatitis group showed the presence of more male infants. Of all the laboratory parameters investigated, the levels of only one enzyme, gamma-glutamyl transferase (GGT), differed significantly between the groups, indicating its possible value as a parameter helping to distinguish between these conditions. They found significant histopathological characteristics which can be helpful in differentiating these two bile duct diseases. Cases of biliary atresia had marked bile ductular proliferation and severe fibrosis, whereas the degree of bile duct loss differed among the groups. In particular, the mean portal tracts with bile duct loss were significantly greater in cases of intrahepatic bile duct paucity (about 74%) than those of neonatal hepatitis (about 39%) and the difference was of strong statistical significance (p < 0.001). These data underline that bile ductular proliferation, loss of bile ducts and advanced fibrosis are key findings helping to distinguish between neonatal cholestatic diseases. Due to the fact that loss of bile ducts is also frequently observed in infants with neonatal hepatitis, it is advisable to apply a higher bar during the diagnostics. Specifically, the diagnosis of intrahepatic bile duct paucity ought to entail the loss of bile duct in over two-thirds of portal tracts to prevent false diagnosis. To conclude, meticulous histological evaluation of the level of bile ductular proliferation, the extent of bile duct loss and the stage of fibrosis can give useful data in differentiating between biliary atresia, intrahepatic bile duct paucity, and neonatal hepatitis. It is necessary to implement more stringent definitions of bile duct loss to make an accurate diagnosis of intrahepatic bile duct paucity, which will enhance the making of proper treatment decisions and outcomes in infants with neonatal cholestasis.